Biodiversity Accounting Disclosure, Climate Governance, and Environmental Risk Management: Their Effect on Corporate Reputation - Maria Yovita R. Pandin; Gita Lidyawati Safitri; Alif Fa'is Nurfadila; Anora Rajwa Erbana; Maretha Wiriaqni Utama; Nanda Nanda; Najwa Bioarti (Lead Journal of Economy and Administration, 2026)
This study aims to explore the effects of Biodiversity Accounting Disclosure (BAD), Climate Governance (CG), and Environmental Risk Management (ERM) on corporate reputation among mining companies listed on the Indonesia Stock Exchange for the 2023–2025 period. Using a quantitative approach, the study draws on secondary data from annual reports and sustainability reports. The sample consists of 25 companies selected via purposive sampling, yielding 75 observations. The data were analyzed using multiple linear regression. The results indicate that the level of biodiversity disclosure and the practice of environmental risk management have a positive and significant relationship with corporate reputation. In contrast, climate governance does not exhibit a significant effect. Collectively, the three independent variables significantly explain variation in corporate reputation, with an Adjusted R² of 30.3%. These findings underscore the importance of transparency in biodiversity reporting and the effectiveness of environmental risk management in strengthening corporate image.